Evaluasi penguasaan kompetensi profesional guru produktif Teknik dan Bisnis Sepeda Motor Sekolah Menengah Kejuruan swasta Kabupaten Sleman - Prayogo, Udin Suryo; Susatya, Edhy; Kuat, Tri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to determine the competency standards for TBSM teachers in the Sleman area, to describe the competency standards for TBSM teachers, to map the professional competencies of TBSM teachers based on the Center for Development and Empowerment of Educators and Education Personnel in the Automotive and Electronics Sector BBPMPPV BOE Malang. This research method uses discrepancy. The research results show (1) The educational background of TBSM teachers in Sleman Regency Vocational Schools is still not in accordance with government regulations (2) The average teacher professional mastery score is 469.7 points or 78, which means the professional mastery of 19 teachers is in the competent category. The results of individual acquisition of teacher professional competence in the quite competent category were 1 person, 16 people in the competent category, and 2 in the very competent category. It can be concluded that no teachers are not yet competent. (3) The obstacle to increasing teacher competency is teacher participation in training; of the 19 teachers, 8 have participated in training, while 11 people have never participated.